SYSTEMATIC LITERATURE REVIEW: INTEGRASI KONSEP TEOREMA PYTHAGORAS DALAM KEGIATAN BELAJAR BERSAMA ALAM - Mukhlesi Yeni, Ety; Nurhayati; Putri Salehha, Osey (Amalgamasi: Journal of Mathematics and Applications, 2025)
Education is an essential process aimed at developing the individual’s potential holistically, encompassing intellectual, emotional, and social aspects. The School of Nature, as an innovative approach to education, uses nature as the primary learning medium, offering relevant contextual experiences for students. SMP Sekolah Alam Bireuen (SABIR) implements the "Learning Together with Nature" (BBA) method, which invites students to learn through direct interaction with their surrounding environment. This approach aims to bridge the gap between theory and practice, while enhancing the understanding of mathematical concepts, including the Pythagorean Theorem. The Pythagorean Theorem, often considered abstract, can be taught more applicably through nature-based learning. This study uses the Systematic Review (SR) method to analyze literature related to the integration of the Pythagorean Theorem in BBA. The analysis results show that nature-based contextual approaches are effective in improving students' mathematical understanding, while also providing an enjoyable and meaningful learning experience. Students not only learn theory but also apply mathematical concepts in the field, such as measuring the sides of right-angled triangles, thus enhancing their understanding and problem-solving skills. This approach also instills values such as cooperation, responsibility, and environmental love, which support the holistic development of student competencies. This research is expected to serve as a reference for the development of nature-based learning methods in the context of more contextual and applicable mathematics education